Application of Zigbee Technology for monitoring enviromental variables in greenhouses - Suárez Barón, Juan Carlos (2013)
This paper describes the application of the Zigbee standard for the development of a Wireless Sensor Networks (WSN) based system, which is used for monitoring environmental variables in greenhouses. This development allows to connect multiple wireless devices for the sake of transmitting variables such as temperature and relative humidity. The Zigbee platform was made in three stages: 1) hardware development, which includes the analysis and hardware selection; 2) construction of a network and the integration of sensors; and, 3) evaluation, in order to define the specifications of each node and scope of communication.